Determinación de los requerimientos hídrico del cultivo de maíz amarillo duro (Zea mays L.), Var. Tusilla, mediante el método del lisímetro volumétrico, en el sector San José, perteneciente al sistema de riego Campana-Malacatos - Guayanay Calva, Francisco Xavier (2019)
The investigation was carried out in the sector San José, belonging to the parish of Malacatos, Loja, the field work was carried out from December 2016, until May 2017. The main objective of this research was to assess the needs water from the cultivation of corn (Zea mays L.), Var. Tusilla, with the purpose of improving the efficiency of water use; For this, Evapotranspiration of the reference culture (ETo) was determined, through the application of the Penman-Monteith method; Evapotranspiration of the corn crop (ETc), using the Volumetric Lysimeter method; and, the Coefficient of culture (Kc) for the phenological phases of the same one. The experimental area was 50 m2, within which 2 lysimeters of 1 m2 of area each were installed. For the cultivation the variety of corn was used Tusilla, the distance of sowing between rows was 0.80 m between rows and 0.80 m between plants, with a density of 15625 plants per hectare. Three grains per crop were sown and thinning was done when the plants reached an approximate height of 30 cm. Within each lysimeter, 4 plants were established (2 grains per stroke). The results of the reference evapotranspiration (ETo) calculated with the Penman-Monteith formula inserted in the Cropwat program were the following: 4.9 mm / day for the VE phase, for the V1 phase 5.1.1 mm / day, phase V2 4.8 mm / day, phase V3 4.4 mm / day, development phases (V4-V12) 4.5 mm day, phase R0 4.5 mm / day, phase R1 4.5 mm / day, phase R2 4.4 mm / day, phase R3 4.3 mm / day, phase R4 3.9 mm / day, by this method we obtain an average of 4.5 mm / day. For the crop evapotranspiration (ETc), determined through the volumetric lysimeter, the following results were obtained: 4.9 mm / day for the VE phase and V1 3.1 mm / day, V2 phase 4 mm / day, phase V3 4.5 mm / day, phases V4 and V9 4.9 mm / day, phases V 10, V11 and V12 4.8 mm / day, phases R0 and R1 4.7 mm / day, phase R2 43.7 mm / day, phase R3 3.5 mm / day, phase R4 3.3 mm / day, by this method we obtain an average of 4.4 mm / day. The coefficient values (Kc) for the crop calculated for each phenological phase were: 0.6 for phase VE and V1, for phase V2 0.8, phase V3 1.0, phases V4-V7 1.1, phase V8 1.0, phases V9-R1 1.1, phases R2-R4 0.8, through these results we obtain an average of Kc equivalent to 0.9. In conclusion, the total water requirement for the entire productive cycle of the maize crop, variety Tusilla is 350.8 mm per m2, which is equivalent to 3508.4 m3 / ha and 3 508 400 lt / ha; the determined yield per hectare has a value of 5309.5 Kg; or 5.3 Tn / ha, therefore the water consumption / yield ratio is 660, 8 liters, which allows to establish that to obtain 1kg of corn, 660, 8 liters of water is required. Keywords: reference evapotranspiration (ETo), crop evapotranspiration (ETc), crop coefficient (Kc), water requirements, volumetric lysimeter.